Accès à la culture biomédicale et enjeux socio-symboliques des représentations de la drépanocytose dans une population scolaire de Guadeloupe - Jérôme Pruneau; Sylvain Ferez; Frédéric Maillard; Berangere Philippon; Olivier Hue (Études Caribéennes)
This paper presents a part of the results of a research on the representation on SCD (Sickle Cell Disease) among a schooled population living in Marie-Galante (Guadeloupe). It treats free associations of the respondents concerning SCD. The analysis of occurrencies and co-occurrencies spontaniously associated to the disease reveals the incertitude surrounding it, attesting thus of a small control of biomedical representations. The status and signification of blood, even as the notion of genetic disease, seem to be ambigious in their answers. They are in fact imbedded in the universe of social and cultural representations related to identity/alterity and filiation problematics.